A Study Of The Effect Of Heat Treatment On Some Mechanical Properties Of Unsaturated Polyester Composites Filled With Particles Of Aluminum Oxide And Carbon Black - ghadir, hiba (Latakia University Journal -Engineering Sciences Series, 2025)
This research aims to study the effect of heat treatment on some mechanical properties (such as frictional properties, wear and surface hardness) of unsaturated polyester composites filled with aluminum oxide (AL2O3) and carbon black (CB) particles. To achieve this goal, samples were prepared by mixing the fillers in different weight fractions and separately with the matrix (unsaturated polyester) using an electric mixer, then the hardener MEPK (methyl ethyl ketone peroxide) was added at a rate of 1.5 % until homogeneity of the mixture mass. After the good mixing process, the composite polymer material was poured into prepared cylindrical molds and left to solidify at room temperature. Then, a heat treatment process was carried out for the composite material samples (UPR composites containing AL2O3 and containing CB) at two temperatures of 60 °C and 80 °C and at different heat treatment times (2, 4, 6, 24) h. The results of the heat treatment showed that a decrease in the volumetric loss values when both the heat treatment time and temperature were increased. In order to verify the validity of the results of the heat treatment effect, the change of surface hardness was studied according to Shore D in terms of the treatment regime followed.